1994
DOI: 10.1080/1073161x.1994.10467245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NO2Measurement Methods for Indoor Air Quality Applications

Abstract: Measurement of nitrogen dioxide (N0 2 ) and other oxidized nitrogen compounds in indoor environments can present some measurement difficulties not normally encountered in sampling outdoor air. This paper examines three methods that are in current use for monitoring indoor nitrogen dioxide. The methods include ozone-based and luminol-based chemiluminescence, and an electrochemical technique. We have examined these methods for accuracy, linear dynamic range, and interferences. Each of the methods was subject to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…CO2 was also measured in a common room between the other two locations but generally closer to the kitchen. NO2 was inferred as the difference between NOX and NO, even though that value likely includes non-negligible amounts of nitrous acid (HONO) (Spicer et al, 1994).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…CO2 was also measured in a common room between the other two locations but generally closer to the kitchen. NO2 was inferred as the difference between NOX and NO, even though that value likely includes non-negligible amounts of nitrous acid (HONO) (Spicer et al, 1994).…”
Section: Overviewmentioning
confidence: 99%
“…The instruments used to measure each of these parameters are noted in Table 6. The values reported for NO2 are based on the difference between measured NOX and NO, and likely include HONO (Spicer et al, 1994); for simplicity, we refer to the NO2 value reported by the instrument as NO2 throughout the remainder of this report. 1 L1=kitchen, L2=central; L3=distant.…”
Section: Air Quality Measurementsmentioning
confidence: 99%
“…This technique provides for highly selective and very sensitive monitoring of these acids in air. 20 - 22 Detection limits are approximately 0.5 ppb for HONO and 50 ppt for HNO 3 .…”
Section: Dining Roommentioning
confidence: 99%
“…The signal from this instrument was corrected for nonlinear response. 20 Nitrous acid (HONO) and nitric acid (HNO 3 ) were monitored using an atmospheric pressure chemical ionization (APCI) tandem mass spectrometer, the TAGA 6000 manufactured by Sciex, Inc. We used a flow rate of 40 L-min 1 through 3/4 in. diameter Teflon tubing to minimize the residence time of the sample air in the tubing, thereby minimizing adsorptive loss of the acids.…”
Section: Dining Roommentioning
confidence: 99%
“…has been used to measure HONO, for example, by the addition of to the source region in order to form the CCl 4 (HONO AE Cl)~adduct. 33 Relative gas phase acidities also support adduct formation between Br~and HOCl. Hydrobromic acid kJ (*H acid \ 1354 mol~1) has a lower dissociation energy than HOCl (*H acid \ kJ mol~1) so that proton transfer from HOCl to Br~is 1502 not expected.…”
Section: Iiid Quantifying Hocl Using Bromoform As the CI Reagent Gasmentioning
confidence: 96%